Kinerja Aparatur Kelurahan Di Wilayah Kecamatan Banjarbaru Utara Dalam Pelayanan Publik - Sitindaon, Helmi Sarlianna (Pahlawan Jurnal Pendidikan-Sosial-Budaya, 2024)
Public service is a form of a country's responsibility to its citizens, which implicitly is the ability of the bureaucracy itself as a public servant who has the legitimate power to regulate society fairly and wisely. To provide excellent service by the government bureaucracy, of course one of the important indicators to build is establishing the performance of government organizations that are able to provide excellent service so that the public feels well served. The aim of this research is to find out how the sub-district apparatus in the North Banjarbaru District of Banjarbaru City performs in public services. The type of research used is policy research with a qualitative descriptive type. The results of the research show that the dimensions of quality of service work are not yet optimal regarding the mastery of expertise and skills in the field of work for the apparatus. Representatively, in the knowledge dimension, there is a tendency such as social programs that are still not on target. Representatively, in the knowledge dimension, there is a tendency such as social programs that are still not on target. The reliability of the reliability dimension regarding apparatus work discipline, service certainty, rights and obligations as well as conditions regarding service comfort need to be re-evaluated. Implementation of the dimensions of presence and cooperation intensity is still not good internally by the sub-district and community members.